Nutrient and aflatoxin contents of traditional complementary foods consumed by children of 6–24 months - Alamu, Emmanuel Oladeji; Gondwe, T.N.P.; Akello, J.; Sakala, N.; Munthali, G.; Mukanga, M.; Maziya-Dixon, B.B. (Wiley, 2018)
The nutrient composition and safety of complementary foods have recently become areas of concern, especially with regard to aflatoxin contamination which has been found to adversely affect health outcomes. This study presents the nutrient and aflatoxin contents of complementary foods consumed by children (6–24 months) and infants and young child feeding practices of mothers from two districts in eastern and southern Zambia. A total of 400 mother–child pairs were recruited from Monze and Chipata districts, and data on breastfeeding and complementary feeding practices were collected twice at 3‐month interval using a structured questionnaire. Samples of two traditional complementary foods (Maize Nshima and Maize porridge) were collected from the mothers and analyzed for nutrient contents and aflatoxin contamination. The results showed that there is a high level of awareness on exclusive breastfeeding among mothers. Fat, protein, carbohydrate, and ash contents of Maize nshima from Chipata were significantly lower (p < .05) compared to those from Monze district except for starch and sugar. Monze mothers preferred to prepare a thicker Maize nshima and Maize porridge compared to their Chipata counterparts. The aflatoxin contamination showed that the Maize porridge samples from Chipata were the most contaminated with mean aflatoxin content of 5.8 ± 15.93 mg/100 g, while Maize nshima was the most contaminated of the two complementary foods from Monze districts with mean aflatoxin level of 3.8 ± 6.41 mg/100 g. There were significant (p < .05) positive correlations between fat and aflatoxin contents for Chipata samples (r = .12409) and for Monze samples (r = .13666). The traditional complementary foods studied were found to be low in fat and protein and high in aflatoxin contamination. Thus, it is imperative that best practices and interventions are designed and introduced to reduce the possible lethal health implications of consumption of such complementary foods by children under 5 years.